2017
DOI: 10.1007/5584_2017_70
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-Forming Ability and Clonality in Acinetobacter baumannii Strains Isolated from Urine Samples and Urinary Catheters in Different European Hospitals

Abstract: An evolution towards a decrease in adhesion ability and a CHDL content change was observed along the years in several European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Ec5FSL and Ec9FSL isolates were grown overnight at 37 • C in Luria-Bertani (LB) broth. Quantitative biofilm production assay was performed as described in Vuotto et al [11]. Each plate was incubated for 20 h at 37 • C, and experiments were repeated three times.…”
Section: Quantitative Biofilm Production Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Ec5FSL and Ec9FSL isolates were grown overnight at 37 • C in Luria-Bertani (LB) broth. Quantitative biofilm production assay was performed as described in Vuotto et al [11]. Each plate was incubated for 20 h at 37 • C, and experiments were repeated three times.…”
Section: Quantitative Biofilm Production Assaymentioning
confidence: 99%
“…[8]. It is increasingly common, especially in hospitalized patients, to isolate from their urines multidrug-and extensively drug-resistant microorganisms, such as extended-spectrum beta-lactamase (ESBL)-producing bacteria, AmpC β-lactamases producers, and carbapenem-resistant Enterobacteriaceae [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, A. baumannii might persist in clinical devices and hospital environments, thus causing HAIs and outbreaks worldwide [ 95 , 114 ]. Supporting this, several studies have reported biofilm formation ability in A. baumannii strains causing various types of infection: surgical site and wound infections [ 115 , 116 ], urinary tract infections [ 117 , 118 ], blood and respiratory infections, and skin and soft infections [ 119 , 120 , 121 ].…”
Section: Clinical Impact Of a Baumannii Biofilmsmentioning
confidence: 79%
“…Except for sputum samples, AB strains isolated from urine or urinary catheters samples have been previously reported [ 35 , 36 ]. Only 8 of 109 CR-AB strains in our study were proved to be strong or moderate biofilm producers, suggesting that it may be related to the nature of the A. baumannii clinical isolates [ 33 ].…”
Section: Discussionmentioning
confidence: 99%